Tradução, adaptação transcultural e validação do banco de itens mobilidade pediátrica do Patient-Reported Outcomes Measurement Information System (PROMIS®) para a língua portuguesa - Kaminice, Aline Tavares Duarte (2016)
This study aimed to translate into Portuguese, culturally adapt and validate the Pediatric Mobility Item Bank of the Patient-Reported Outcomes Measurement Information System (PROMIS®). The coordinators of PROMIS® followed the universal translation process based on the Functional Assessment of Chronic Disease Therapy (FACIT), which consisted of eight stages. This methodology promoted the semantic and conceptual maintenance of this item bank from English to Portuguese. The final version was a self-applied questionnaire, which 1019 participants answered. The validation process consisted in checking the psychometric properties to assess the adequacy of the linguistic and cultural content of the items for the Brazilian population and included the analysis of data quality, reliability, validity, and calibration of the items through the Item Response Theory. The semantic and conceptual structure of PROMIS® Pediatric Mobility Item Bank did not change between the pretest and the final version. In the assessment of the data quality, we observed floor effect in eight items and ceiling effect in all items; the instrument presented adequate reliability demonstrated by means of the Cronbach's alpha coefficient and the intraclass correlation coefficient, both higher than 0.97. The factor loadings were representative, which indicates that the items fitted well to the model. Among the participants, 484 answered the same response categories at the ends of the latent trait continuum, and 929 respondents chose the same answer category in the item 4190R1 - "I could turn the whole head to the side”. Depending on the concentration of responses in the extreme categories, the item 4190R1 and the 484 participants were excluded to perform the calibration of the psychometric properties through the IRT analysis. The version for the Portuguese PROMIS® Pediatric Mobility Item Bank presented correspondence with the original items after the process of translation and cultural adaptation confirmed by the evaluation of the psychometric properties.